PROFESIONALISME GURU SEBAGAI PILAR UTAMA PENINGKATAN MUTU PENDIDIKAN - Muhammad Jalaluding; Kartini Rahman Nisa (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
Teacher professionalism plays a crucial role in a success of learning and the improvement of educational quality at SMKN 1 Talibura. Teachers are required to perform their duties optimally by mastering four core competencies: pedagogical, professional, social, and personality. This study used a qualitative descriptive approach with semi-structured interviews, classroom observations, and literature review. The observations showed that teachers prepare lesson plans and teaching modules according to the characteristics of vocational students, combining theory with practice, discussions, and simple work simulations. Evaluations are conducted individually, tailored to students’ abilities. Professional competence is demonstrated through proficiency in the subject and ongoing self- formation via MGMP meetings and online training. Social competence is reflected in open communication with students, additional mentoring, and active coordination with parents. Meanwhile, personality competence is evident in teachers’ discipline, exemplary behavior, and ability to maintain a conducive classroom environment. This study is innovative in its integration of contextualized learning grounded in the characteristics of the vocational school, where teacher professionalism is reflected not only through meeting formal standards but also through creative adaptation to local conditions and student needs. These four competencies are interrelated and form the foundation for holistic teacher professionalism. ABSTRAK Profesionalisme pendidik menjadi faktor utama dalam keberhasilan pembelajaran dan peningkatan mutu pendidikan di SMKN 1 Talibura. Guru di tuntut melaksanakan tugas secara optimal dengan menguasai empat kompetensi yaitu kemampuan pedagogik, keahlian profesional, keterampilan sosial, dan aspek kepribadian. Metode yang diterapkan adalah pendekatan kualitatif dengan desain penelitian deskriptif melalui wawancara semiterstruktur, observasi langsung, dan kajian pustaka. Hasil observasi menunjukkan bahwa guru merancang Rencana Pelaksanaan Pembelajaran dan bahan ajar yang disesuaikan dengan kebutuhan peserta didik kejuruan, memadukan teori dengan praktik, diskusi, dan simulasi kerja sederhana. Evaluasi dilakukan secara personal, menyesuaikan kemampuan siswa. Kompetensi profesional terlihat dari penguasaan materi dan upaya pengembangan diri melalui MGMP dan pelatihan daring. Kompetensi sosial tercermin dari komunikasi terbuka dengan siswa, pendampingan tambahan, dan koordinasi dengan orang tua. Sementara itu, kompetensi kepribadian tampak dari kedisiplinan, keteladanan, dan kemampuan menjaga suasana kelas kondusif.  Kebaruan temuan penelitian ini terletak pada integrasi pembelajaran kontekstual berbasis karakteristik sekolah kejuruan, di mana profesionalisme guru tercermin tidak hanya melalui pemenuhan standar, tetapi juga adaptasi kreatif terhadap kondisi lokal dan kebutuhan siswa. Keempat kompetensi saling mendukung dan menjadi fondasi profesionalisme guru secara utuh.